2020
DOI: 10.1667/rade-20-00093.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous In Utero Low- and Medium-Dose-Rate Gamma-Ray Exposure on Fetal Germ Cells

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In mammalian fetal testes, germ cells are cells with the greatest sensitivity to ionizing radiation (RAD) [3,42,43]. Doses as low as 0.1 Gy during germ cell proliferation cause DNA double strand breaks (DSBs) and induces cell death by apoptosis [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian fetal testes, germ cells are cells with the greatest sensitivity to ionizing radiation (RAD) [3,42,43]. Doses as low as 0.1 Gy during germ cell proliferation cause DNA double strand breaks (DSBs) and induces cell death by apoptosis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the negative impact of postnatal irradiation at doses higher than 1 Gy on human and rodent Leydig cells and androgen production [8,9,[11][12][13][14]. To our knowledge, very few studies have examined the long-term effect of testicular exposure to radiation in utero on adult Leydig cells [43,[67][68][69], and most of these studies have reported no obvious effect. In this study, we provide the first evidence that fetal exposure to radiation has an endocrine disrupting effect independent of direct action on estrogen and androgen receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Cells that divide rapidly are more vulnerable to radiation than those cells that divide at a slower rate. The germ cells supporting the growth and maturation of the oocytes are more radiosensitive than the stromal cells that give structural support to the ovary [32].…”
Section: Factors Affecting Ovarian Radiosensitivitymentioning
confidence: 99%
“…Similar studies of the effects of chronic irradiation on animals were carried out after the nuclear accident at the Chernobyl nuclear power plant [8,9,10,11,12,13]. Most of the mentioned studies were aimed at assessing the general physiological, environmental and population parameters of animals [14,15]. However, the question still remains of assessing the effect of radiation on reproductive organs, gametes and the development of embryos.…”
Section: Introductionmentioning
confidence: 99%